The Transparency of Evil in The Leftovers and its Implications for Student (Dis)engagement. Issue 1 (2nd January 2016) - van Kessel, Cathryn
Abstract : The HBO series, The Leftovers, provides a thought-provoking platform for discussing Baudrillard's conceptualization of evil and the implications for contemporary pedagogical discourse about student (dis)engagement. The dystopic scenario of 2% of the world's population suddenly disappearing might help us rethink our own society, including education. Baudrillard distinguishes between a creative Evil force that can be positive or negative in its outcome and a moral evil seen as wholly negative. By examining the situation created by the modern confusion of evil and misfortune, it becomes apparent that disengagement moves beyond personal characteristics. Unveiling such underlying issues allows for a reconceptualization of youth at risk, and thus has repercussions for the explanation of disengaged youth in our classrooms.